Assessing the health effects of a "no deal" Brexit. (29th August 2019) - van Schalkwyk, May C I; Barlow, Pepita; Stuckler, David; Rae, Maggie; Lang, Tim; Hervey, Tamara; McKee, Martin
Abstract : Leaving the EU without a deal is a leap in the dark. May van Schalkwyk and colleagues call for a full evaluation of the health effects and suggest what it should cover